Examining the Impact of Store Atmosphere, Self-Reward Behavior, and Supporting Facilities on Customer Loyalty in Coffee Shops: A Study in Medan - Louis, James; Panggabean, Esther Praja Anggriany (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya (UPR), 2026)
The rapid growth of the coffee shop industry in urban Indonesia has intensified competition, making customer loyalty a critical factor for business sustainability and long-term profitability. In this context, understanding the determinants of customer loyalty has become increasingly important, particularly in emerging metropolitan markets such as Medan City. This study aims to examine the effects of store atmosphere, self-reward behavior, and supporting facilities on customer loyalty among coffee shop customers in Medan. The study adopts a causal quantitative research design using a survey method. Data were collected through an online questionnaire distributed to coffee shop customers who had visited at least twice within the last month. Using a purposive sampling technique, a total of 170 valid respondents were included in the main analysis. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The findings reveal that all proposed variables exert a positive and statistically significant influence on customer loyalty. Specifically, store atmosphere significantly affects customer loyalty (β = 0.392; p < 0.001), indicating that environmental attributes such as lighting, music, layout, and aesthetics contribute to repeat visit intentions. Self-reward behavior also demonstrates a significant positive effect (β = 0.384; p < 0.001) and emerges as the strongest predictor with the largest effect size (f² = 0.361), suggesting that coffee shop visits are strongly associated with emotional gratification and personal appreciation. In addition, supporting facilities, including WiFi quality, seating comfort, and access to charging outlets, significantly influence customer loyalty (β = 0.230; p = 0.001). Collectively, the three variables explain 73.0% of the variance in customer loyalty (R² = 0.730), indicating strong explanatory power. These findings contribute to the customer loyalty literature by integrating experiential, psychological, and functional dimensions within a single framework. Practically, the study suggests that coffee shop managers should implement integrated strategies that enhance atmospheric quality, emotional customer experience, and supporting facilities to strengthen long-term customer retention.